Perlindungan Hukum bagi Para Pihak dalam Perjanjian Jual Beli Tanah Letter C dibawah Tangan - Aprilio, Zulfikar Madyasta; Silviana, Anna (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The agreement made in the private sale and purchase of Letter C land constitutes a legal relationship between the two parties. Legal relationship is a relationship that gives rise to legal consequences guaranteed by laws and regulations. Every legal action that gives rise to legal consequences must receive legal protection, especially if there is a dispute between the parties. Disputes can occur after a private agreement on the sale of Land Letter C is agreed. This study aims to analyze and understand the law given to the parties involved in private agreements on Letter C land sellers, where protection can usually be obtained from clauses in the agreement and outside the agreement in statutory regulations. Legal protection is an important aspect to guarantee the fulfillment of one's legal rights. Legal protection is needed to provide solutions, certainty and clarity to existing settlements and potential post-agreement disputes. The research method used is the normative juridical research method. The approach used is the statutory approach. The primary legal material collection is by collecting regulations and examining all laws and regulations related to the research problem. From the results of this study, it is illustrated that protection for the seller is asking the buyer to immediately pay the price of the object of the agreement within a certain period of time. Based on Articles 1513 and 1514 of the Civil Code, the protection that can be exercised by the buyer in executing a sale and purchase agreement is to examine the existence of proof of ownership of the land rights that are the object of the agreement. The buyer is based on Article 1491 of the Civil Code.